FRI0445 Faecal calprotectin, but not anti-saccharomyces cerevisiae antibodies, is linked to worse disease status in axial spondyloarthritis patients without inflammatory bowel disease: results from the spartakus cohort. (15th June 2017) - Olofsson, T; Mogard, E; Andréasson, K; Marsal, J; Geijer, M; Kristensen, L-E; Lindqvist, E; Wallman, JK
Abstract : Background: Inflammatory bowel disease (IBD) is a common comorbidity in axial spondyloarthritis. Objectives: To study faecal calprotectin (F-calprotectin) levels and anti- Saccharomyces cerevisiae antibodies (ASCA) and their associations with disease status and gastrointestinal (GI) symptoms in axial spondyloarthritis. Methods: Consecutive patients with a clinical axial spondyloarthritis diagnosis were examined and classified as non-radiographic axial spondyloarthritis (nr-axSpA; Assessment of SpondyloArthritis international Society [ASAS] criteria; n=26) or ankylosing spondylitis (AS; modified New York criteria; n=45). Only patients without known IBD were included. F-calprotectin and ASCA IgA and IgG antibodies in serum were measured by commercially available enzyme-linked immunosorbent assay kits (Calpro AS; ORGENTEC Diagnostika). Results: Elevated levels of F-calprotectin (≥50 mg/kg) were observed in 15% of nr-axSpA and 40% of AS patients (non-significant difference, with reservation for small groups). Overall, worse mean disease activity/disability scores were observed among patients with elevated versus normal F-calprotectin levels (Table), whereas no association was seen between F-calprotectin and GI symptoms. Similar results remained after exclusion of patients with monoclonal antibody type anti-TNF therapy. Elevated levels of ASCA IgA were observed in 8%/2% of nr-axSpA/AS patients, and IgG in 28%/26%. Only 2 subjects were ASCA double positive. Neither disease activity/disability measures nor GI symptoms were associated with ASCA status. Conclusions: Elevated levels of F-calprotectin and ASCA IgG antibodies are both common in axial spondyloarthritis patients without IBD, and elevated F-calprotectin may be a marker of more severe spondyloarthritis. Neither F-calprotectin nor ASCA levels were associated with self-reported GI symptoms. Disclosure of Interest: T. Olofsson: None declared, E. Mogard: None declared, K. Andréasson: None declared, J. Marsal Grant/research support from: AbbVie, Ferring, Hospira, Consultant for: AbbVie, Ferring, Hospira, MSD, Pfizer, Takeda, Tillotts, UCB, M. Geijer: None declared, L.-E. Kristensen Grant/research support from: Oak Foundation, Consultant for: AbbVie, Celgene, BMS, MSD, Novartis, Pfizer, UCB, E. Lindqvist: None declared, J. Wallman Consultant for: Celgene, Novartis, UCB